Serotonin Transporter Binding and Genotype in the Nonhuman Primate Brain using [C-11]DASB PET - Christian, BT (2009)
The length polymorphism of the serotonin (5-HT) transporter gene promoter region has been implicated in altered 5-HT function and, in turn, neuropsychiatric illnesses, such as anxiety and depression. The nonhuman primate has been used as a model to study anxiety-related mechanisms in humans based upon similarities in behavior and the presence of a similar 5-HT transporter gene polymorphism. Stressful and threatening contexts in the nonhuman primate model have revealed 5-HT transporter genotype dependent differences in regional glucose metabolism. Using the rhesus monkey, we examined the extent to which serotonin transporter genotype is associated with 5-HT transporter binding in brain regions implicated in emotion-related pathology. METHODS: Genotype data and high resolution PET scans were acquired in 29 rhesus (macaca mulatta) monkeys. [C-11]DASB dynamic PET scans were acquired for 90 minutes in the anesthetized animals and images of distribution volume ratio (DVR) were created to serve as a metric of 5-HT transporter binding for group comparison based on a reference region method of analysis. Regional and voxelwise statistical analysis were performed with corrections for anatomical differences in gray matter probability, sex, age and radioligand mass. RESULTS: There were no significant differences when comparing 1/1 homozygotes with s-carriers in the regions of the brain implicated in anxiety and mood related illnesses (amygdala, striatum, thalamus, raphe nuclei, temporal and prefrontal cortex). There was a significant sex difference in 5-HT transporter binding in all regions with females having 18% – 28% higher DVR than males. CONCLUSIONS: Because these findings are consistent with similar genotype findings in humans, this further strengthens the use of the rhesus model for studying anxiety related neuropathologies.